If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -24 = 3x + 4 Reorder the terms: -24 + 5x = 3x + 4 Reorder the terms: -24 + 5x = 4 + 3x Solving -24 + 5x = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -24 + 5x + -3x = 4 + 3x + -3x Combine like terms: 5x + -3x = 2x -24 + 2x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 -24 + 2x = 4 + 0 -24 + 2x = 4 Add '24' to each side of the equation. -24 + 24 + 2x = 4 + 24 Combine like terms: -24 + 24 = 0 0 + 2x = 4 + 24 2x = 4 + 24 Combine like terms: 4 + 24 = 28 2x = 28 Divide each side by '2'. x = 14 Simplifying x = 14
| 5x^2+15x-5=0 | | 1/3y=8 | | 3-(1)/(3x^2/3)=0 | | 5y+3-3= | | 18-(7x)=80 | | 1000x^3-50x^2-50x=1050 | | 1000.89x^3-50x^2-50x=1050 | | 2n^2+n=9-2n | | (64)^-2/3 | | 1050x^3+50x^2+50x=1000 | | -5x+y=-16 | | 1050x^3+50x^2+50x=1000.892899 | | 21x^3+x^2+x-1000.892899=0 | | 5x=-3x+28 | | -x^2-2x=15 | | -x^2-2x^2=15 | | x^(2/3)=3.2 | | y-2x-9/(-2,3) | | (78.90)^1/6 | | (7.890)^1/6 | | 7x+35=70 | | Yx-6x=11 | | -3(q+2)= | | (3)-((1)/(3x)^(2/3)) | | Y+x+y=24 | | 3-(1/3x^2/3) | | 5n+2(8n-7)= | | 3-((1)/(3x)^2/3) | | 3w+11=-8+51 | | 3-1/3x^2/3 | | -2=-6w+2(w-3) | | 16(2x-7)=4(8x+9) |